Utilization of the Safe Surgical Dislocation Approach of the Hip to Retrieve a Bullet from the Femoral Head. (19th December 2011) - Delaney, Ruth; Albright, Maurice; Rebello, Gleeson
Abstract : Retained intra-articular missiles from low-velocity handguns can lead to mechanical arthritis, synovitis, and lead toxicity. Various surgical approaches have been described to extract such foreign bodies from the hip joint. We present the case of a 17-year-old male in which the surgical dislocation approach was utilized to retrieve a bullet from the femoral head with a good short-term outcome. This case represents a rare application of the surgical hip dislocation approach for an unusual trauma.